The Impact of Compensation towards Employees' Performance: Employees’ Motivation as the Mediating Role (The Spectrum, 2023)
This research identifies the impact of compensation on employees' job performance. The study used a causal-comparative research design to explore the relationship between compensation and employee performance in commercial banks. The sample size was calculated using a formula that determined the appropriate sample size for the population of 385 employees. The survey questionnaire was administered to 192 employees out of 20 branches of 15 commercial banks, and respondents' demographic information was collected. The study found that both financial and non-financial compensation significantly affect employees' job performance. Additionally, employee motivation was found to have a mediating role between compensation and job performance. The findings of this research have implications for organizations to design compensation and benefits schemes that can help to increase employee motivation and job performance.